Analysis of the effect of childhood stress on the expression of serotonin system genes in the hippocampus and cortex in adult male rats - Faress, Fardad; Esfanjani, Mitra; Esfanjani, Mina (Technium BioChemMed, 2022)
Reflects an interaction between genetic susceptibility and environmental factors such as stress are likely underlying neurobiology of major depression. Various factors have been proposed in anxiety behaviors caused by childhood stress, but the role of 5HT-3 and 5HT-2c receptors in its occurrence has been less investigated. Excessive expression of related genes in the brain is associated with the formation of anxiety behaviors (1-3). In this research, six pregnant rats were used. After giving birth, their babies experience separation stress from their mothers, called Maternal Neonatal Separation or childhood stress. This article aims to investigate the effect of childhood stress on 5HT-3 and 5HT-2c gene expression in the hippocampus and cortex and the possible effects of exercise on anxiety behaviors and 5HT-3 and 5HT-2c gene expression in the hippocampus and cortex in male rats. This article showed that voluntary exercise during adolescence can reduce the of these gene expression in the brain and has a protective role against stress.